Assessing the situation of cities from the perspective of urban crisis management components (Case study: Shirvan city) - Mehdi Mohammadzadeh moghafam; mohammad motamedi; Ezzatollah Mafi (تحقیقات کاربردی علوم جغرافیایی)
According to the issues raised, the present study has been compiled with the aim of examining and assessing the situation of cities from the perspective of urban crisis management components. The research method in this research is a combination of research, applied (using the results and output of research in Shirvan) and development; Statistical population In the present study, according to the determination and classification of related organizations, each organization was selected as a statistical sample from each organization according to the percentage of the total statistical population, which in total 227 People were selected as the statistical sample of the present study. Finally, the quota non-probability sampling method, in which the number of samples is determined in advance and is from experts, was distributed. The findings show that the lowest and most unfavorable calculated average of 3.57 belongs to the post-crisis period and post-crisis reconstruction, which is not in a satisfactory state. It is related to the identification of vulnerable zones due to hazards in Shirvan city and in this section 12 indicators were analyzed based on FAHP model, which showed that the rate of vulnerability in 5.37% of Shirvan city Very low, 22.38% low vulnerability, 14.12% moderate vulnerability, 27.75% high vulnerability and 30.39% very high vulnerability. In fact, it can be said that the vulnerability of Shirvan is low in 27.75% of the city and high in 58.14% of the city. In the central neighborhoods of the city due to high age, population density, wear and tear, low quality buildings and ... the level of vulnerability is high.